A GoZayaan’s report introducing digitization in customer experience: impacts of automation services to overcome the challenges in streamlining processes - Hossain, Sheneen (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.